The paradox and tension of moral claims: Evangelical Christianity, the politicization and globalization of sexual politics in sub-Saharan Africa - Kaoma, Kapya (Critical research on religion, 2014)
This article explores the paradox between local and global moral values in sexual politics in Sub-Saharan Africa. It shares the thesis that various forces of globalization—the web, media, social, economic, political, and religious--influence and to some extent shape sexual politics in Sub-Saharan Africa. Globalization has made it easy for anti-gay and pro-gay rights groups to connect globally, and share ideas and strategies, but it has also complicated the study of sexual politics in Sub-Saharan Africa. While anti-gay and pro-gay groups accuse each other of being “influenced by foreign interests,” both sides have global groups that provide the ideological framework for the struggle. To some extent, the growing opposition to gay rights should be understood from the perspective of conservative global Christianity on one hand and the globalization on the other. The article concludes that global anti-gay activism invites global pro-gay activism, thereby leading to unintended consequences on sexual minorities.